Overview of Immune Response During SARS-CoV-2 Infection: Lessons From the Past - Shah, Vibhuti Kumar; Firmal, Priyanka; Alam, Aftab; Ganguly, Dipyaman; Chattopadhyay, Samit (Frontiers in Immunology, 2020)
After the 1918 flu pandemic, the world is again facing a similar situation. However, the advancement in medical science has made it possible to identify that the novel infectious agent is from the coronavirus family. Rapid genome sequencing by various groups helped in predicting the structure and function of virus, immunogenicity in diverse populations and its preventive measures. Coronavirus attacks the respiratory system causing pneumonia and lymphopenia in infected individuals. Viral components like spike, nucleo-capsid proteins trigger an immune response in the host to eliminate the virus. These viral antigens can be either recognized by B cells or presented by MHC complexes to T cells resulting in antibody production, increased cytokine secretion and cytolytic activity in the acute phase of infection. Association of HLA and its downregulated expression has been correlated with disease severity against influenza and coronaviruses. Studies have reported that infected individuals after recovery can induce strong protective responses by generating a memory T cell pool against SARS-CoV and MERS-CoV. These memory T cells were not persistent for long term and upon reactivation caused local damages due to cross-reactivity. So far the reports suggest that SARS-CoV-2, which is highly contagious shows related symptoms in 3 different stages and develops an exhaustive T cell pool in higher loads of viral infection. As there are no specific treatments available for this novel coronavirus, numerous small molecular drugs which are being used for the treatment of diseases like SARS, MERS, HIV, ebola, malaria and tuberculosis are under clinical trials for controlling COVID-19. A classical immunotherapy of convalescent plasma transfusion from recovered patients has also been initiated for neutralization of viremia in terminally ill COVID-19 patients. Due to the limitations in plasma transfusion, researchers are now focusing on developing neutralizing antibodies against virus particles along with immuno-modulation of cytokines such as IL-6, TNF-α and interferons that could help in combating the infection. This review highlights the similarities of SARS-CoV, MERS-CoV and SARS-CoV-2 in relation to their pathogenicity and immunogenicity and also focuses on various treatment strategies which could be employed for curing COVID-19.